A comparison of the incidence of supraventricular arrhythmias between thoracic paravertebral and intercostal nerve blocks in patients undergoing thoracoscopic surgery: A randomised trial. Issue 10 (October 2018) - Wu, Caineng; Ma, Wuhua; Cen, Qingyun; Cai, Qingxiang; Wang, Jiyong; Cao, Ying
Abstract : BACKGROUND: Postoperative supraventricular arrhythmias are common in patients after thoracoscopic lobectomy. Inadequate pain control has long been recognised as a significant risk factor for arrhythmias. The performance of ultrasound-guided (USG) thoracic paravertebral block (PVB) is increasing as an ideal technique for postoperative analgesia. OBJECTIVE: We conducted this study to evaluate whether a single-shot USG thoracic PVB would result in fewer postoperative supraventricular tachycardias (SVT) than intercostal nerve blocks (ICNBs) after thoracoscopic pulmonary resection. DESIGN: A randomised controlled study. SETTING: A single university hospital. PATIENTS: Sixty-eight patients undergoing thoracoscopic lobectomy were randomised into two equal groups of 34. INTERVENTIONS: For postoperative pain control, all patients received a total of 0.3 ml kg −1 of a mixture containing 0.5% ropivacaine and 1/200 000 epinephrine after placement of needles for either a single thoracic PVB or two individual ICNBs, both guided by ultrasound. Data were obtained during the first 48 postoperative hours. MAIN OUTCOME MEASURES: The primary outcome was the incidence of SVT after thoracoscopic pulmonary resection. RESULTS: During the first 48 postoperative hours, the incidences of SVT and atrial fibrillation were lower in the USG thoracic PVB group (14.7 vs. 46.9%, P  = 0.004 and 3.0 vs. 18.8%, P  = 0.037, respectively). The requirement for β-receptor blockade was more frequent in the ICNBs group than in the PVB group (5.9 vs. 25%, P  = 0.033). CONCLUSION: After placement of the needle using ultrasound guidance, a single-shot thoracic PVB is a well tolerated and effective technique to reduce the incidences of postoperative SVT and atrial fibrillation in patients undergoing thoracoscopic pulmonary resection. TRIAL REGISTRATION: http://www.chictr.org/cn/, registration number: ChiCTR-IOR-17010952.